Outer Membrane Protein 49,4 Kda dari Porphyromonas gingivalis Merupakan Protein Hemaglutinin dan Adhesin Terhadap Netrofil - Mubarokah, Siti Nurul; Sumarno, Sumarno; Muliartha, I Ketut Gede (Jurnal Kedokteran Brawijaya, 2009)
ABSTRACTPeriodontitis is caused mostly by P. gingivalis and it is related to acute coronary syndrome. P. gingivalis readilyinvades into blood circulation and potentially induces. Collagenolytic activity of neutrophil which result incollagen vascular degradation lead to atherosclerotic plague rupture (APR). APR is responsible for occurringfatal cardiovascular events such as acute myocardial infarction (AMI). These information brought out notionconcerning the adhesion interaction of P. gingivalis with neutrophil. The aim of this study was to assessadhesion molecule of P. gingivalis outer membrane protein (OMP) by partial characterization took inhemagglutination assay using mice erythrocytes, adhesion inhibition assay by gradual concentration ofadhesion blocked in neutrophil, immunologic assay using Western-blotting and immunocytochemistry. Theresults showed that 49,4 kDa P.gingivalis OMP can agglutinate mice erythrocytes and adherence to netrophilIncrease concentration of OMP P. gingivalis 49,4 kDa reduce adhesion process to netrophil This protein wasrecognized by the polyclonal antibody of 49,4 kDa adhesion molecule. It can be concluded that P gingivalisouter membrane protein is a hemagglutinin and an adhesion molecule to netrophilKeywords : 49,4 kDa P. gingivalis OMP, neutrophil, hemagglutination, adhesin